Comparison of the reading understanding in the students of 1° to 3ér. degree of primary of state and noncstate centers educative of Lima metropolitan - Delgado Vásquez, Ana Esther (2004)
OBJETIVES: a. To study children's reading comprehension development of first to third grade of primary school. b. To analyze the comprehension developmental level of public and private schools students of first, second and third grade of primary school. c. To compare the reading comprehension level considering student's sex on first, second and third grade. d. To set the instruments psychometrics properties. e. To study the reading comprehension model using the confirmatory factor analysis.